Bioactive compounds in tomato and their roles in disease prevention - Shah, Kabita Kumari; Modi, Bindu; Lamsal, Bibek; Shrestha, Jiban; Aryal, Surya Prasad (Fundamental and Applied Agriculture, 2021)
Tomato (Lycopersicum esculentum L.) is an excellent source of many nutrients and secondary metabolites that are important for human health. Its fruits are rich in antioxidant compounds, which are important for human metabolism. Lycopene is one of the abundantly occurring antioxidants found in tomato. Lycopen is beneficial in preventing various chronic diseases such as can- cer, cardiovascular diseases etc. Tomato is an important source of bioactive compounds which have antioxidant, anti-mutagenic, anti-proliferative, anti- inflammatory and anti-atherogenic activities. A group of vitamins (ascorbic acid and vitamin A), phenolic compounds (phenolic acids and flavonoids), carotenoids (lycopene, α, and β carotene), and glycoalkaloids (tomatine) are found in tomato. These compounds can provide protection to our health by neutralizing free radicals which are responsible for the growth of a range of degenerative diseases. The present review provides collective informa- tion on the pharmacological actions and chemistry of bioactive compounds (carotenoids, lycopene, β –carotene, lutein, and vitamins) found in tomato along with discussing possible health benefits.